The Impact of the China Coast Guard on Indo-Pacific and Southeast Asia Security from the Perspective of a Maritime Power - Chao, Jiun-chuan (Center for Southeast Asian Social Studies (CESASS), 2023)
In 2024, the China Coast Guard (CCG) invoked China Coast Guard Regulation No. 3 to detain Taiwanese fishing boats in disputed waters twice. These actions can be dated back to 2019. The CCG entered the waters of the Diaoyu islands in Japan twelve times and carried out cruises on the Diaoyu islands. It is necessary to study the follow-up actions of the CCG and their impact on Indo-Pacific and Southeast Asia security. This study examines the effect of the CCG's maritime rights protection on the security of the Indo-Pacific region and Southeast Asia when the People's Republic of China (China) becomes a maritime power. It was changed to the Maritime Police Corps of the Chinese People's Armed Police Force to integrate the business of marine surveillance, fishery administration, customs, border defense, and other units. The reason for the gradual expansion of powers and the impact of its strong protection of maritime rights and interests on Indo-Pacific and Southeast Asia. The research results can help us understand the current situation of the CCG and further evaluate China's ability to achieve maritime power. This paper finds that China intends to implement regular patrols in disputed waters by increasing the tonnage of coast guard ships, strengthening rights protection, and militarizing organizations to demonstrate maritime power. On the other hand, this move triggered a maritime police competition among neighboring countries, and even a naval and air force arms race, intensified disputes between China and neighboring countries, especially the South China Sea dispute, and made the security of the Indo-Pacific region and Southeast Asia be more turbulent.